Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3390/ijms13010097
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Tools and Novel Challenges in Long Non-Coding RNAs (lncRNAs) Functional Analysis

Abstract: The advent of next generation sequencing revealed that a fraction of transcribed RNAs (short and long RNAs) is non-coding. Long non-coding RNAs (lncRNAs) have a crucial role in regulating gene expression and in epigenetics (chromatin and histones remodeling). LncRNAs may have different roles: gene activators (signaling), repressors (decoy), cis and trans gene expression regulators (guides) and chromatin modificators (scaffolds) without the need to be mutually exclusive. LncRNAs are also implicated in a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 83 publications
2
72
0
2
Order By: Relevance
“…However, different ncRNA-specific databases are now publicly accessible, and these are of great help in their study: lncRNAdb (Amaral et al 2011;Quek et al 2015), providing detailed information about lncRNA, which includes sequences, functions, expression patterns, cellular location, and interacting proteins; NONCODE (Xie et al 2014), which accounts for other types of sequences than lncRNAs and with similar information as the p r e v i o u s m e n t i o n e d ( C h e n e t a l . 2 0 1 3 ) ; LncRNADisease , presenting data that associate lncRNAs with diseases, namely, with cancer ; and other lesser known databases (Da Sacco et al 2012). Nevertheless, these databases are scarce regarding the information about satncRNAs, and the NONCODE database is the only one with data regarding these sequences.…”
Section: The Analysis Of Satncrnas-experimental Approachesmentioning
confidence: 98%
“…However, different ncRNA-specific databases are now publicly accessible, and these are of great help in their study: lncRNAdb (Amaral et al 2011;Quek et al 2015), providing detailed information about lncRNA, which includes sequences, functions, expression patterns, cellular location, and interacting proteins; NONCODE (Xie et al 2014), which accounts for other types of sequences than lncRNAs and with similar information as the p r e v i o u s m e n t i o n e d ( C h e n e t a l . 2 0 1 3 ) ; LncRNADisease , presenting data that associate lncRNAs with diseases, namely, with cancer ; and other lesser known databases (Da Sacco et al 2012). Nevertheless, these databases are scarce regarding the information about satncRNAs, and the NONCODE database is the only one with data regarding these sequences.…”
Section: The Analysis Of Satncrnas-experimental Approachesmentioning
confidence: 98%
“…It has been shown that the transcription of lncRNAs can affect the expression of nearby coding genes (Da Sacco et al, 2012). LncRNAs can recruit chromatinmodifying enzymes to regulate the expression of genes, either in cis (near the site of lncRNA production) or in trans (when the genes involved are distant) through a phenomenon called transvection (Da Sacco et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs can recruit chromatinmodifying enzymes to regulate the expression of genes, either in cis (near the site of lncRNA production) or in trans (when the genes involved are distant) through a phenomenon called transvection (Da Sacco et al, 2012). In our study, the lncRNAs that displayed the greatest decrease in expression in H2 were the lincRNAs TSPAN8 and CALCA; the nearby genes encoding TSPAN8 and CALCB mRNA were also differentially expressed in the H2 and LM3 cell lines and the fold change in their expression was equally high (48.58408 and 74.100555, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are popular in molecular studies due to their critical functions in regulating diverse biological behaviors [7]. In addition, it has been disclosed that lncRNAs are also key regulators in various cardiovascular diseases (heart failure in particular); these lncRNAs include lncRNA CHRF [8], lncRNA H19 [1], lncRNA HOTAIR [9], and others.…”
Section: Introductionmentioning
confidence: 99%